Comprehensive mechanical power analysis in sprint running acceleration - Pavei, G.; Zamparo, P.; Fujii, N.; Otsu, T.; Numazu, N.; Minetti, A. E.; Monte. A. (Scandinavian Journal of Medicine & Science in Sports, 2019)
Sprint running is a common feature of many sport activities. The ability of an athlete to cover a distance in the shortest time relies on his/her power production. The aim of this study was to provide an exhaustive description of the mechanical determinants of power output in sprint running acceleration and to check whether a predictive equation for internal power designed for steady locomotion is applicable to sprint running acceleration. Eighteen subjects performed two 20 m sprints in a gym. A 35-camera motion capture system recorded the 3D motion of the body segments and the body center of mass (BCoM) trajectory was computed. The mechanical power to accelerate and rise BCoM (external power, Pext) and to accelerate the segments with respect to BCoM (internal power, Pint) were calculated. In a 20 m sprint, the power to accelerate the body forward accounts for 50% of total power; Pint accounts for 41% and the power to rise BCoM accounts for 9% of total power. All the components of total mechanical power increase linearly with mean sprint velocity. A published equation for Pint prediction in steady locomotion has been adapted (the compound factor q accounting for the limbs' inertia decreases as a function of the distance within the sprint, differently from steady locomotion) and is still able to predict experimental Pint in a 20 m sprint with a bias of 0.70±0.93 W·kg-1. This equation can be used to include Pint also in other methods that estimate external horizontal power only